Oral Health Attitude of General Population & their Dental Treatment Choices: A Cross Sectional Study in Hyderabad - Hassan Shahid, Munaza Qadri, Navaid 7 Sadia Hassan , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To assess the oral health attitude of general population in Hyderabad and their dental treatment choices. Study Design: cross sectional study Place & Duration: Out Patient Department (OPD) of Isra Dental College. Hyderabad from I " July 2014 to 31' August 2014. Material and Methods: This study included 2056 patients attending the Out Patient Department (OPD) of Isra Dental College. The information concerning different study variables including their demographic data, reason for visiting the dental OPD and treatment choices, was obtained on a questionnaire. SPSS version-21 was used for data analysis and variables were expressed in frequencies and percentages. Moreover, chi square test was used for categorical variable. Results; Out of the 2056 patients in this study, 55.9% (n=1149) and 44.1% (n=907) were male and female respectively. Most of the patients were above 40 years of age 46.8% (n=963). It was found that dental pain was the most common reason for visiting the Dental OPD (n=1324; p=.001). Most of the patients preferred to save the tooth and opted for Root Canal Treatment (n=470; p=<0.001), Conclusion: Attitude and treatment choices of patients reflect educated behavior and knowledge as a large amount of the people favored Root Canal Treatment however, a noticeably number of them opted for extraction over saving the tooth, There is need of improvement in spreading awareness about dental hygiene and better treatment options by involvement of dental health professionals.